The Role of Microglial CX3CR1 in Schizophrenia-Related Behaviors Induced by Social Isolation - Zhou, Hao; Wang, Jiesi; Zhang, Yu; Shao, Feng; Wang, Weiwen (Frontiers in Integrative Neuroscience, 2020)
According to the microglial hypothesis of schizophrenia, the hyperactivation of microglia and the release of proinflammatory cytokines lead to neuronal loss, which is highly related to the onset of schizophrenia. Recent studies have demonstrated that fractalkine (CX3CL1) and its receptor CX3CR1 modulate the function of microglia. Thus, the present study aimed to determine whether microglial CX3CR1 plays a role in schizophrenia-related behaviors. A classical animal model of schizophrenia, social isolation (from postnatal days 21 to 56), was used to induce schizophrenia-related behaviors in C57BL/6J and CX3CR1-/- mice, and the expression of the microglial CX3CR1 protein was examined in several brain areas of the C57BL/6J mice by Western blot analysis. The results revealed that social isolation caused deficits in the prepulse inhibition (PPI) in the C57BL/6J mice but not in the CX3CR1-/- mice and increased locomotor activity in both the C57BL/6J mice and the CX3CR1-/- mice. Moreover, the CX3CR1 protein level was increased in the medial prefrontal cortex, nucleus accumbens, and hippocampus of the C57BL/6J mice. These findings suggested that the function of microglia regulated by CX3CR1 might participate in schizophrenia-related behaviors.